A Translation Analysis of English Modal Verb in Alice in Wonderland Film and Its Translation - WIGIYANTI, ARSIH WENDA (2012)
This study aims to explain the variation of translating English modal verb in Alice in Wonderland subtitle and its translation, to identify dominant translation variation of English modal verbs and to describe the meaning of English modal verb translated into Indonesian. This type of this research is descriptive qualitative reserch. The method of collecting data is comparing method of English document by selecting English modal verb which can be found in the Alice in Wonderland subtitle and its translation. The results of the study show that firstly, there are three variations of translation English modal verb. They are English modal verb translated into adjective consist of 16 data or 8%, 21 data or 11% English modal verb translated into adverb and 157 data or 81% English modal verb translated into Indonesian modal verb. Secondly, the dominant translation variation of English modal verbs in Alice in Wonderland subtitle is English modal verbs are translated into Indonesian modal verb. It can be shown that, 157 data or 81% English modal verb translated into Indonesian modal verb. Thirdly, there are seven the variety meanings of English modal verbs and its translation, namely, ability meaning, 40 data or 21%, possibility meaning 17 data or 9%, futurity meaning 57 data or 29%, certainty meaning 38 data or 20%, obligation meaning 37 data or 19%, willingness meaning 2 data or 1%, permission meaning 3 data or 2%.